Antiviral Properties of Basidiomycetes Metabolites - A. V. Avtonomova; L. M. Krasnopolskaya (Антибиотики и Химиотерапия, 2020)
The data on the antiviral action of the Ganoderma lucidum, Lentinus edodes, Grifola frondosa, Agaricus brasiliensis and other basidiomycetes metabolites are summurized. The metabolites of these species of basidiomycetes exhibit a direct antiviral effect on herpes simplex virus types I and II, human immunodeficiency virus (HIV), hepatitis B virus, vesicular stomatitis virus, influenza virus, Epstein-Barr virus, and others. Moreover, metabolites of basidiomycetes increased antiviral immunity.